Preliminary investigation of the eruption time of kimberlite in the Late Devonian in Mengyin, Shandong - Tian, Ruicong; Wang, Haiqin; Tian, Jingxiang; Shan, Wei; Wang, Xiufeng; Chi, Naijie; Ma, Xiaodong; Chu, Zhiyuan; Li, Shenghu; Lv, Qing (Frontiers in Earth Science, 2023)
Kimberlite in the Mengyin area serves as an excellent medium for studying the characteristics and evolutionary processes of the Paleozoic mantle. In order to determine the age of the primary calcite within the kimberlite, in situ carbonate U–Pb dating was conducted in the Mengyin area. The results indicate that the primary calcite in the kimberlite originated approximately 383 ± 18 Ma (MSWD = 6.6). This age constraint suggests that the eruption of the kimberlite took place during this period, leading to the thermal alteration of limestone xenoliths, ultimately forming marble. Consequently, it can be inferred that lithospheric thinning occurred no later than the Late Devonian period. Fluid inclusions found within the marble provide further insights into its formation. The recorded formation temperature of the marble ranges from 243°C to 370°C, with a salinity range of 2.57%–14.77% (NaCl). The pressure estimates fall within the range of 3.22–20.70 MPa, indicating a depth mainly between 900 and 1,000 m. Based on these findings, it can be inferred that the overall denudation depth in the west Shandong area, since the Late Devonian, is estimated to be approximately 900–1,000 m. Furthermore, the overall crustal rise rate is estimated to be approximately 3 m/Ma.